Answer:
A: 244 pounds
B: 122 pounds
C: 274 pounds
Step-by-step explanation:
We have A+B+C = 640; A=2B; C=A+30. Substituting the last into the first gives ...
A + B + (A +30) = 640
2A +B = 610 . . . . . . . . . . . . subtract 30
Substituting the second into this equation gives ...
2(2B) +B = 610
B = 610/5 = 122 . . . . . divide by 5
A = 2B = 244 . . . . . . . .find A from B
C = A+30 = 274 . . . . . find C from A
Box A weighs 244 pounds; box B weighs 122 pounds; box C weighs 274 pounds.
Answer:
k12
Step-by-step explanation:
Recall that zeroes can be transformed into factors by subtracting them from x. This gives us the following factors:
(x - 1)(x + 3)(x - 4)
Now, if you multiply the first two factors together, you get the following:
(x² + 2x - 3)
Multiply that by the last factor, (x - 4), and you get this:
(x³ + 2x² - 3x - 4x² - 8x + 12)
This can be simplified:
(x³ - 2x² - 11x + 12)
And there's your final answer. Hope this helped!
Answer:
Part A = 90
Part B = 145
Step-by-step explanation:
For part A, we know that a triangle has a sum of 180 degrees. So we just add the angles we already know and then subtract them from 180. For part B, we know that angle ACB and angle ACD are supplementary angles, meaning they add up to 180 degrees. So just take 180 and subtract 35 to find the measure of angle ACD.